2013
DOI: 10.1016/j.diabres.2013.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Euglycemic progression: Worsening of diabetic retinopathy in poorly controlled type 2 diabetes in minorities

Abstract: Aims In type 2 diabetes, early effects of strict near-normalization of glucose control on macrovascular and microvascular disease are still uncertain. We evaluated the effects of early dramatic improvement in glycemia on retinal disease in poorly controlled diabetes. Methods A retrospective, case-control study in public hospital patients with type 2 diabetes, who had annual retinal imaging as part of a case management program or standard diabetes care. Patients included had ≥2 two retinal images ≥1 one year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 15 publications
4
34
2
Order By: Relevance
“…This meant that tight glycemic control might positively influence microangiopathy development. Such conclusions are in contrast with those coming from Shurter et al [45] who observed a progressive worsening of diabetic retinopathy in case-control study involving type 2 diabetes. In particular, the authors observed that a tight glycemic control improve the progression of retinopathy from baseline (+0.7+0.25 units, p=0.015), while the standard glycemic control group did not showed any significant change in the progression of their eye disease as compared to baseline (0.03 + 0.14 units, p = NS) [45].…”
Section: Pre-diabetes and Early Impairment In Cardiovascular Systemcontrasting
confidence: 55%
See 1 more Smart Citation
“…This meant that tight glycemic control might positively influence microangiopathy development. Such conclusions are in contrast with those coming from Shurter et al [45] who observed a progressive worsening of diabetic retinopathy in case-control study involving type 2 diabetes. In particular, the authors observed that a tight glycemic control improve the progression of retinopathy from baseline (+0.7+0.25 units, p=0.015), while the standard glycemic control group did not showed any significant change in the progression of their eye disease as compared to baseline (0.03 + 0.14 units, p = NS) [45].…”
Section: Pre-diabetes and Early Impairment In Cardiovascular Systemcontrasting
confidence: 55%
“…Such conclusions are in contrast with those coming from Shurter et al [45] who observed a progressive worsening of diabetic retinopathy in case-control study involving type 2 diabetes. In particular, the authors observed that a tight glycemic control improve the progression of retinopathy from baseline (+0.7+0.25 units, p=0.015), while the standard glycemic control group did not showed any significant change in the progression of their eye disease as compared to baseline (0.03 + 0.14 units, p = NS) [45]. Chilelli et al [46] proposed a "glycoxidationcentric" theory: rather than glycemic control, AGEs control is the best way to reduce the burden of microangiopathy in diabetic patients.…”
Section: Pre-diabetes and Early Impairment In Cardiovascular Systemcontrasting
confidence: 55%
“…Early worsening was also demonstrated in a retrospective case‐control study in 68 public hospital patients with type 2 diabetes, predominantly from ethnic minorities (Latino/other). These patients underwent annual retinal imaging either as part of a case management programme or as standard diabetes care . An “intensive” group of patients (n = 34) with an HbA1c decrease of more than 1.5% was compared with randomly chosen (control) patients (n = 34) with minimal HbA1c changes over 2 years.…”
Section: Early Worsening In Type 2 Diabetesmentioning
confidence: 99%
“…Results of prospective case-control studies and randomized controlled clinical trials have shown that bariatric surgery results in remission of Type 2 diabetes in~80% of cases [1]. However, there is concern that rapid lowering of glycaemia may cause a paradoxical worsening in diabetic retinopathy [3,4], as observed during intensive management in pregnancy [5,6], insulin pump therapy [7], GLP-1 analogues [8,9] and after pancreatic transplantation [10,11]. It is well known that lowering glycaemia can slow the development and progression of diabetic retinopathy in the long term [2].…”
Section: Introductionmentioning
confidence: 99%